Tea tree oil for Demodex blepharitis - Savla, Keyur (Cochrane Database Syst Rev, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the effects of tea tree oil on ocular Demodex infestation in people with chronic Demodex blepharitis.